Sudden unexpected death caused by stroke: A nationwide study among children and young adults in Denmark. Issue 3 (April 2018) - Ågesen, Frederik Nybye; Risgaard, Bjarke; Zachariasardóttir, Sára; Jabbari, Reza; Lynge, Thomas Hadberg; Ingemann-Hansen, Ole; Ottesen, Gyda Lolk; Thomsen, Jørgen Lange; Haunsø, Stig; Krieger, Derk Wolfgang; Winkel, Bo Gregers; Tfelt-Hansen, Jacob
Background: Stroke is the fifth leading cause of death in young individuals globally. Data on the burden of sudden death by stroke are sparse in the young. Aims: The aim of this study was to report mortality rates, cause of death, stroke subtype, and symptoms in children and young adults who suffered sudden death by stroke. Methods: We conducted a retrospective, nationwide study including all deaths within Danish borders between 2000–2009 and 2007–2009 in persons aged 1–35 years and 36–49 years, respectively. Two physicians identified all sudden death cases through review of all death certificates. All available autopsy reports and records from hospitals and general practitioners were retrieved and a neurologist identified all sudden death by stroke cases. Results: Of the 14, 567 deaths in the 10-year period, there were 1, 698 sudden death cases, of which 52 (3%) were sudden death by stroke. There was a male predominance (56%) and the median age was 33 years. The incidence of sudden death by stroke in individuals aged 1–49 years was 0.19 deaths per 100, 000 person-years. Stroke was hemorrhagic in 94% of cases, whereof subarachnoid hemorrhage was the cause of death in 63% of cases. Seventeen (33%) cases contacted the healthcare system because of neurological symptoms, whereof one was suspected of having a stroke (6%). Conclusions: Sudden death by stroke in children and young adults occurs primarily due to hemorrhagic stroke. We report a high frequency of neurological symptoms prior to sudden death by stroke. Increased awareness among healthcare professionals towards stroke symptoms in children and young adults may lead to earlier detection of stroke, and thereby potentially lowering the incidence of sudden death by stroke.